2022
DOI: 10.1590/1678-4499.20210267
|View full text |Cite
|
Sign up to set email alerts
|

Genetic-molecular characterization in guava full-sib progeny

Abstract: Brazil is one of the world's largest producers of guava (Psidium guajava L.), a very promising fruit in the northern region of the state of Rio de Janeiro. Despite this, no guava cultivar has been developed for the region. Thus, this study proposed to examine a population of guava full sibs using microsatellite markers and to identify which genotypes are the most divergent for future crosses, to select cultivars better adapted to the soil and climatic conditions of northern Rio Janeiro. Ninety-six superior gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…In the studied populations, the utilized markers showed an average of 4 alleles per locus, which were lower than those reported by De Oliveira et al (2022), Chiveu (2018), Mehmood et al (2016) and higher than those reported by Kumar et al (2023), Oliveira et al (2022), Kumar et al (2020), Kherwar et al (2018), and similar to that reported by Chaithanya et al, 2014. The total number of guava alleles found was 39, a result similar to that obtained by Kumar et al (2023), which could be attributed to Wahlund effect (Martín, 2017), the self-pollinating behavior of the species due to possessing perfect flowers, which aids in self-fertilization (Kumari et al, 2018), and to the extent of the populations used in each of the studies (Díaz et al, 2022).…”
Section: Discussion Discussion Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In the studied populations, the utilized markers showed an average of 4 alleles per locus, which were lower than those reported by De Oliveira et al (2022), Chiveu (2018), Mehmood et al (2016) and higher than those reported by Kumar et al (2023), Oliveira et al (2022), Kumar et al (2020), Kherwar et al (2018), and similar to that reported by Chaithanya et al, 2014. The total number of guava alleles found was 39, a result similar to that obtained by Kumar et al (2023), which could be attributed to Wahlund effect (Martín, 2017), the self-pollinating behavior of the species due to possessing perfect flowers, which aids in self-fertilization (Kumari et al, 2018), and to the extent of the populations used in each of the studies (Díaz et al, 2022).…”
Section: Discussion Discussion Discussioncontrasting
confidence: 75%
“…The average number of effective alleles (Ne) was 3.2, which was lower than that obtained by Mehmood et al (2016), higher than that reported by Kumar et al (2023), Oliveira et al (2022) and similar to that obtained by Sitther et al (2014).…”
Section: Discussion Discussion Discussionmentioning
confidence: 40%